The impact of historical redlining on neurosurgeon distribution and reimbursement in modern neighborhoods - Jean-Luc K. Kabangu; John E. Dugan; Benson Joseph; Amanda Hernandez; Takara Newsome-Cuby; Danny Fowler; Momodou G. Bah; Lane Fry; Sonia V. Eden; Sonia V. Eden (Frontiers Media S.A., 2024)
BackgroundThis study examines the lasting impact of historical redlining on contemporary neurosurgical care access, highlighting the need for equitable healthcare in historically marginalized communities.ObjectiveTo investigate how redlining affects neurosurgeon distribution and reimbursement in U.S. neighborhoods, analyzing implications for healthcare access.MethodsAn observational study was conducted using data from the Center for Medicare and Medicaid Services (CMS) National File, Home Owner's Loan Corporation (HOLC) neighborhood grades, and demographic data to evaluate neurosurgical representation across 91 U.S. cities, categorized by HOLC Grades (A, B, C, D) and gentrification status.ResultsOf the 257 neighborhoods, Grade A, B, C, and D neighborhoods comprised 5.40%, 18.80%, 45.8%, and 30.0% of the sample, respectively. Grade A, B, and C neighborhoods had more White and Asian residents and less Black residents compared to Grade D neighborhoods (p < 0.001). HOLC Grade A (OR = 4.37, 95%CI: 2.08, 9.16, p < 0.001), B (OR = 1.99, 95%CI: 1.18, 3.38, p = 0.011), and C (OR = 2.37, 95%CI: 1.57, 3.59, p < 0.001) neighborhoods were associated with a higher representation of neurosurgeons compared to Grade D neighborhoods. Reimbursement disparities were also apparent: neurosurgeons practicing in HOLC Grade D neighborhoods received significantly lower reimbursements than those in Grade A neighborhoods ($109,163.77 vs. $142,999.88, p < 0.001), Grade B neighborhoods ($109,163.77 vs. $131,459.02, p < 0.001), and Grade C neighborhoods ($109,163.77 vs. $129,070.733, p < 0.001).ConclusionHistorical redlining continues to shape access to highly specialized healthcare such as neurosurgery. Efforts to address these disparities must consider historical context and strive to achieve more equitable access to specialized care.